Electron mobility and mode analysis of scattering for β-Ga2O3 from first principles. (25th August 2020) - Ma, Jinlong; Meng, Fanchen; Xu, Dongwei; Hu, Run; Luo, Xiaobing
Abstract: The electrical transport properties of β-Ga2 O3 are studied by first-principles calculations. The calculated intrinsic electron Hall mobilities agree well with experiments, with intrinsic Hall factor decreasing monotonically from 1.54 at 100 K to 1.14 at 800 K. The anisotropy of electron mobility is weak due to the almost isotropic electron effective mass, which also results in nearly isotropic Seebeck coefficient and electronic contribution to the thermal conductivity. The mode analysis of phonon scattering reveals that the optical phonon scattering is almost entirely determined by the long-range polar interactions, whereas the acoustic phonon scattering also plays an important role especially at low temperatures. The intrinsic electron mobility is significantly overestimated even above room temperature by only considering the polar optical phonon scattering, in contrast to previous predictions from fitting of phenomenological models.